Tight cohesion between glycolipid membranes results from balanced water–headgroup interactions - Matej Kanduč (Nature Portfolio, 2017)
Glycolipids are commonly found in densely stacked biological membranes, which show unusually strong self-cohesion compared to phospholipid membranes. Here, the authors attribute this phenomenon to the lack of long-range repulsion between glycolipid membranes, a consequence of the headgroup architecture.